Strange body in upper airways - Ángel Onel Valón Rodriguez; Ana María Daudinot Borrero (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a year-old child is presented who was assisted in the Pediatrics Service of the Serrekunda Hospital in Gambia for presenting breathing difficulty for 2 days, cough and lack of air, all of them of fast beginning. Taking into account the possible presence of a strange body in the high breathing ways a meticulous physical exam was carried out that included the laryngoscope, but due to its deep location it was not possible a correct observation of it, reason why other studies were indicated (magnetic resonance and endoscopy) that allowed a correct visualization of this body.  Due to the multidisciplinary and opportune treatment, the patient had a favorable clinical course and was discharged without complications.